APPEARANCE,BUILD UP AND SPREAD OF LATE BLIGHT IN RELATION TO SOURCE OF INOCULUM - S. K. BHATTACHARYYA, B. P. SINGH AND (Indian Phytopathology, 2002)
Appearance, build up and spread of late blight in relation to source of inoculum were studied at the Central Potato Research Institute, Shimla for three years (1984-86) using infector plant as source of inoculum. Disease first appeared on the 'infector' and within 7·8 days primary infection focus was formed around the infec!or. A disease gradient was formed with maximum DI at the source (infector) which decreased with the increase in distance. Mixed plantings of susceptible and resistant cultivars in 1 : 3 to 1 : 4 ratio reduced the disease progress by 2·2.5 times. Prognosis of late blight based on spore appearance was not possible as P. infestans spores always appeared after (0·3 days) the disease. Under glasshouse studies, tubers carrying infection upto 10 per cent of the surface area served as source of inoculum. Disease expression in plants raised from infected tubers was generally at the stern base excepting few plants which exhibited disease symptoms at varying plant levels.